Hubungan Riwayat Bullying (Korban) Tradisional dengan kejadian Cyberbullying pada Mahasiswa: The Relationship of Traditional Bullying History (Victimization) with the Incidence of Cyberbullying in College Students - Paul Joae Brett Nito; Onieqie Ayu Dhea Manto; Dewi Wulandari (Fakultas Keperawatan Universitas Andalas, 2022)
Bullying is a major problem for teenagers that becomes a barrier to achieving the SDGs, bullying has a negative impact on both victims and perpetrators. The effects of bullying include psychological, social problems, decreased academic performance, and even suicide. The development of technology does not only have a positive impact, but also a negative impact. One of them is the increasing incidence of online bullying or cyberbullying. UNICEF (2016), victims of cyberbullying in Indonesia reached 41-50%. Almost every day 80% of Indonesian teenagers are reported to be victims of cyberbullying. The aimed of this study was to determine the relationship between a history of traditional bullying and the incidence of cyberbullying in college students. An analytical survey method with a cross sectional survey design was conducted among 196 respondents. Cyberbullying and Online Aggression Survey questionnaires was used to measure the cyberbullying. The relationship between the history of traditional bullying and the incidence of cyberbullying in student was analyzed using chi square test. The results of the statistical test show p value < 0.05. The conclusion of this study, there was a significant relationship between the history of traditional bullying and the incidence of cyberbullying in students. The experience of bullying that still occurs among children needs to be further improved in providing support to victims and perpetrators so that there are no health problems, both physical and psychological, even causing the influence of social relations with peers.